2020
DOI: 10.1108/tqm-09-2019-0216
|View full text |Cite
|
Sign up to set email alerts
|

Social media usage in Indian beauty and wellness industry: a qualitative study

Abstract: PurposeAdvancement in technology has increased the use of social media among Internet users. People are on social media all day and brands cannot miss this opportunity to turn these users into potential customers. The purpose of this research paper is to identify the prominent social media platforms in Indian beauty and wellness industry and to establish dimensions of social media activities.Design/methodology/approachThis is a qualitative study in which in-depth interviews were conducted with owners and manag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 61 publications
1
20
0
3
Order By: Relevance
“…The use of social media is growing amongst contemporary businesses because it provides a relatively affordable, pervasive, user-friendly, and accessible platform that individuals can use in their private lives (Högberg, 2018;Högberg & Olsson, 2019;Kaur & Kumar, 2020). Social media is very beneficial for small businesses, which often have limited resources to market their products (Barnes et al, 2012).…”
Section: Social Media and Small Businessmentioning
confidence: 99%
“…The use of social media is growing amongst contemporary businesses because it provides a relatively affordable, pervasive, user-friendly, and accessible platform that individuals can use in their private lives (Högberg, 2018;Högberg & Olsson, 2019;Kaur & Kumar, 2020). Social media is very beneficial for small businesses, which often have limited resources to market their products (Barnes et al, 2012).…”
Section: Social Media and Small Businessmentioning
confidence: 99%
“…Social media, as online technological tools with web 2.0, allows people to interact easily with the online community by exchanging data and sharing information via the Internet [10]. Social media, as one of the digital platforms, is regarded as suited to the character of micro-enterprises.…”
Section: A Micro-enterprises Social Media and Instagrammentioning
confidence: 99%
“…Amongst all social media platforms, Instagram is the prominent one following Facebook. This platform facilitates two-way communication and promotes the business to a broader audience [15]. Compare to the other platforms, Instagram has a higher level of use for interaction, co-creation, and engagement [16].…”
Section: A Micro-enterprises Social Media and Instagrammentioning
confidence: 99%
See 1 more Smart Citation
“…Maintenance of in-store and customer-responsive environment reinforces a positive evaluation of services by the effect of overall grooming given to the customers (Shahbazi and Akareem, 2013;Jung et al, 2017). In the context of beauty salons research has been done on the subjects such as the attitude of women toward beauty salons (Paluri and Mehra, 2019), professionalism in beauty and wellness work (Raval and Pal, 2019), identifying prominent social media platforms in the Indian beauty and wellness industry (Kaur and Kumar, 2020). No study to date has been found investigating servicescape dimensions for beauty salons in India.…”
Section: Introductionmentioning
confidence: 99%